Antibacterial activity of cycas rumphii miq. leaves extracts against some tropical human pathogenic bacteria - Khan, Abdul Viqar; Ahmed, Qamar Uddin; Khan, Athar Ali; Shukla, Indu (Academic Journals, 2011)
Aim of the present study was to explore antibacterial potential of the leaves of Cycas rumphii Miq. The leaves were separately macerated with methanol and double distilled water at room temperature to obtain methanol and aqueous (AQ) extracts. The methanol extract was further successively extracted with light petroleum ether (LPE), benzene (BZ), ethyl acetate (EtOAc) and methanol (MeOH) on hot water bath to get respective extracts. These extracts were evaluated for their antibacterial efficacy at six different concentrations (500 g, 1, 2, 5, 10 and 15 mg ml-1) against seven G+ve and eleven G–ve hospital isolated bacterial strains causing several tropical diseases using disc diffusion method. EtOAc and MeOH extracts showed maximum antibacterial activity against most of the bacteria taken into account. Present findings are suggestive of antibacterial agents in the leaves of C. rumphii which can be used in future for formulation of broad spectrum herbal antibacterial products. Results of present study also support various traditional uses associated with this plant which were suggestive of possible antibacterial potential of this plant. Hence, EtOAc and MeOH extracts of the leaves of C. rumphii deserve further investigations. Keywords: Cycas rumphii, crude extracts, successive extraction, antibacterial activity, Gram-positive bacteria, Gram-negative bacteria